Earbud technology for the blind / Muhammad Syafiq Irfan … [et al.] - -, Muhammad Syafiq Irfan; -, Nor Raimie; -, Muhammad Faris Aiman; -, Muhammad Airil Ashraff; -, Mohammad Raziq; -, Wan Muhammad Faris Akmal (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
This paper explores the innovative use of earbud technology to enhance accessibility for individuals with visual impairments. By integrating advanced features such as voice commands, real-time navigation, and object recognition, earbuds serve as a discreet and intuitive tool for assisting the blind in daily tasks and navigation. This technology not only fosters greater independence but also promotes inclusion and equal participation in various aspects of life for the visually impaired community.